A conceptual schema-based temporal meta database schemas generation technique for 3D objects - Chau, Vo Thi Ngoc; Chittayasothorn, Suphamit (My University, 2010)
In this paper, a temporal meta database for three-dimensional (3D) objects whose properties and relationships are supported by valid time is introduced. Based on our proposed temporal object-oriented conceptual schema model, a conceptual schema of the temporal meta database can be generated from a 3D graphical data source and other particular application requirements. Based on our proposed temporal object relational data model with attribute timestamping, logical schemas of the temporal meta database can be systematically and automatically generated from the conceptual schema. From the temporal meta database, non-temporal/temporal metadata about temporal 3D objects are available for temporal information system users. Convenient access using database languages such as SQL can be performed. Queries over 3D objects using a temporal object relational SQL are demonstrated. © 2009 Springer-Verlag London Limited.
Keywords: 3D object; Conceptual schema model; Metadata; Temporal database; Temporal object relational data model